KAJIAN PENGGUNAAN LIDAH BUAYA (Aloe vera) DAN BEE POLLEN PADA PEMBUATAN SABUN OPAQUE - Ani Suryani, Erliza Hambali dan Hasanah Kurniadewi (Department of Agroindustrial Technology, Bogor Agricultural University, 2005)
ABSTRACTThe Aloe vera gel consists of saponin which is able to control and maintain skin moist. Bee pollen consists of high protein as well as A, B, C, D, and E vitamins used to regenerate skin and to supply some nutrition to the skin. Based on those facts, aloe vera gel and bee pollen could be used in opaque soap which in return could give an additional value and increase selling point and benefit. The best opaque soap is made from the Aloe vera gel with the concentration of 5% and the bee pollen of 5%. The soap characteristics are as follows; moisture content 9,37%; the amount of fatty acid 72,18%; the degree of unsaponifiable fraction 0,43%; insoluble matter in alcohol 0,57%; the degree of free alkali as sodium hydroxide (NaOH) 0,022%; pH 9,35; emulsion stability 96,90% and foam stability 92,95%.Key words : Aloe vera, bee pollen, opaque soap